Discourses on the nuclear deal: persistence of independence - Sullivan, Kate Helen (2008)
In the course of public contestation and debate, political parties in India have attempted to garner acceptance for their respective positions on the Indo-Us nuclear deal by drawing on key historical norms. Notions of freedom, which have historically constituted a primary feature in Indian foreign policy discourse, continue to feature in foreign policy debate and form a focus of consensus and dissent even today in India as it was during the dawn of independence. - Reproduced.
Keywords: Nuclear weapons